Using cholecystokinin to facilitate endoscopic clearance of large common bile duct stones - Tao, Tao (Baishideng Publishing Group Inc, 2014)
AIM: To evaluate the effect of cholecystokinin (CCK) during extracorporeal shockwave lithotripsy (ESWL) in the clearance of common bile duct (CBD) stones in endoscopic retrograde cholangiopancreatography (ERCP). METHODS: Between January 2007 and September 2012, patients with large CBD stones who were treated with ESWL and ERCP were identified retrospectively. Patients were randomized in equal numbers to cholecystokinin (CCK) and no CCK groups. For each CCK case, a dose (3 ng/kg per min for 10 min) of sulfated octapeptide of CCK-8 was administered intravenously near the beginning of ESWL. ERCP was performed 4 h after a session of ESWL. The clearance rate of the CBD was assessed between the two groups. RESULTS: A total of 148 consecutive cases (CCK group: 74, no CCK group: 74) were tallied. Overall there were 234 ESWLs and 228 ERCPs in the 148 cases. The use of CCK showed a significantly higher rate of successful stone removal in the first ESWL/ERCP procedure (71.6% vs 55.4%, P = 0.035), but resulted in similar outcomes in the second (42.8% vs 39.4%) and third (41.7% vs 40.0%) sessions, as well as total stone clearance (90.5% vs 83.8%). The use of mechanical lithotripsy was reduced in the CCK group (6.8% vs 17.6%, P = 0.023), and extremely large stone (≥ 30 mm) removal was higher in the CCK group (72.7% vs 41.7%, P = 0.038). CONCLUSION: CCK during ESWL can aid with the clearance of CBD stones in the first ESWL/ERCP session. Mechanical lithotripsy usage was reduced and the extremely large stone (≥ 30 mm) clearance rate can be raised.